2014
DOI: 10.1088/2043-6262/5/2/025009
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of gold nanoparticles synthesized by γ -irradiation after intravenous administration in mice

Abstract: In the present research work we evaluate the in vivo distribution of gold nanoparticles (AuNPs) at different time durations after intravenous administration in mice. AuNPs with size of about 20 nm and concentration of 1 mM were synthesized by gamma irradiation method using 0.5% alginate as a stabilizer. AuNPs were characterized by UV-Vis spectrum and transmission electron microscope (TEM) image. The as-synthesized AuNPs solution was centrifuged to concentrate to 2 mg AuNPs/1 ml solution. Intravenous administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Our characterization results for AuNPs stabilized in CM-chitosan are in good agreement with those of AuNPs synthesized by irradiation using other stabilizers, such as dextran, hyaluronate, alginate, and chitosan [12,13,[15][16][17][18].…”
Section: Radiation Synthesis and Characterization Of Aunpssupporting
confidence: 81%
See 3 more Smart Citations
“…Our characterization results for AuNPs stabilized in CM-chitosan are in good agreement with those of AuNPs synthesized by irradiation using other stabilizers, such as dextran, hyaluronate, alginate, and chitosan [12,13,[15][16][17][18].…”
Section: Radiation Synthesis and Characterization Of Aunpssupporting
confidence: 81%
“…Luan et al [12] reported that AuNPs stabilized in alginate with an average particle size of about 20 nm synthesized by gamma Co-60 irradiation were not toxic to mice at an injected dose of approximately 33.3 mg/kg body weight and the AuNP/alginate product could potentially be applied as an X-ray contrast agent, especially for the blood and liver. In this study, AuNP/CM-chitosan prepared by irradiation was injected into mice via the tail vein and the distribution in various organs was investigated to understand the in vivo distribution of this AuNP product.…”
Section: In Vivo Distribution Of Aunps/cm-chitosan In Micementioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that after 1 hour of administration, the nanoparticles were mainly accumulated in blood (41.56%), liver (51.60%), lungs (6.16%) and kidneys (0.53%). After 6 hours of administration, the nanoparticles were mainly accumulated in liver (76.33%), lungs (11.86%) and kidneys (2.23%) [86]. Table 2, presents the biodistribution of AuNPs at 24 hours after IV administration in rats and can be observed that in the case of ultrasmall AuNPs, a very high concentration was present in liver, compared to AuNPs with higher dimensions.…”
Section: Biodistribution and Toxicity Aspects Of Gold Nanoparticlesmentioning
confidence: 95%